Digital Transformation and Its Impact on Production Improvement: A Case Study at PT Gajah Mada Plastik - Heri Hardiansyah; Ratih Amelia; Adi Harianto; Ester; Maya Syahlina (Journal of Business Integration Competitive, 2025)
PT Gajah Mada Plastik is a plastic manufacturing company that produces plastic bottles using a make-to-stock system, where finished goods are stored before being sold. However, the company has not implemented effective production planning, leading to a mismatch between production volume and market demand. In February 2024, production exceeded demand, resulting in overstock and increased storage costs. This study aims to conduct demand forecasting and aggregate planning to improve production scheduling in a timely, accurate, and cost-efficient manner. Forecasting is performed using one year of historical sales data to project future demand. Aggregate planning is then calculated using two methods: the level method and the chase strategy. The results indicate that the level method yields the lowest total cost, amounting to Rp 98,207,310. Therefore, the level method is selected for aggregate planning, aligning with the company’s current condition of excess inventory. This approach allows the company to fulfill customer demand effectively while minimizing costs and avoiding further overstock.